Hematopoietic cell transplantation in chronic granulomatous disease: a study of 712 children and adults - Chiesa, Robert; Wang, Junfeng; Blok, Henric-Jan; Hazelaar, Sheree; Neven, Benedicte; Moshous, Despina; Schulz, Ansgar; Hoenig, Manfred; Hauck, Fabian; Al Seraihy, Amal; Gozdzik, Jolanta; Ljungman, Per; et al. (Blood, 2020)
Chronic granulomatous disease (CGD) is a primary immunodeficiency resulting in life-threatening infections and inflammatory complications. Allogeneic hematopoietic cell transplantation (allo-HCT) can cure the disease, but the indication to transplant remains controversial. We performed a retrospective multicenter study of 712 patients with CGD who underwent allo-HCT transplantation from March 1993 through December 2018. We studied 635 children (aged <18 years) and 77 adults. Median follow-up was 45 months. Median age at transplantation was 7 years (range, 0.1-48.6). Kaplan-Meier estimates of overall survival (OS) and event-free survival (EFS) at 3 years were 85.7% and 75.8%, respectively. In multivariate analysis, older age was associated with reduced survival and increased chronic graft-versus-host disease. Nevertheless, OS and EFS at 3 years for patients ≥18 years were 76% and 69%, respectively. Use of 1-antigen-mismatched donors was associated with reduced OS and EFS . No significant difference was found in OS, but a significantly reduced EFS was noted in the small group of patients who received a transplant from a donor with a >1 antigen mismatch. Choice of conditioning regimen did not influence OS or EFS. In summary, we report an excellent outcome after allo-HCT in CGD, with low incidence of graft failure and mortality in all ages. Older patients and recipients of 1-antigen-mismatched grafts had a less favorable outcome. Transplantation should be strongly considered at a younger age and particularly in the presence of a well-matched donor.
Keywords: Granulomatous Disease, Chronic; dítě; lidé středního věku; míra přežití; mladiství; Survival Rate; Prognosis; Retrospective Studies; mladý dospělý; Male; dospělí; transplantace hematopoetických kmenových buněk; retrospektivní studie; chronická granulomatózní nemoc; Follow-Up Studies; lidé; prognóza; následné studie; Hematopoietic Stem Cell Transplantation; Adolescent; Child, Preschool; ženské pohlaví; Young Adult; Infant; homologní transplantace; kojenec; Adult; mužské pohlaví; předškolní dítě; Child; Middle Aged; Humans; příprava pacienta k transplantaci; Transplantation Conditioning; Transplantation, Homologous; Female